Composing Radiographic Dictionary for Radiology Students and Radiographers - Reliyanti, Euis; Damayanti, Oktarina (Research Collaboration Community (Rescollacom), 2023)
The rapid development of science and technology on radiology requires radiology students in particular and radiographers in general to be able to understand and master the science and technology through books or scientific articles, which are mostly written in English. To help them understand the radiological scientific information easily, a complete basic terminologies dictionary on radiology is needed. This study aimed to analyze the vocabularies contained in radiology textbooks linguistically which then are compiled into a radiological pocket dictionary. This research used a qualitative descriptive method. Data were taken in the form of vocabulary list resulted from previous research conducted by the author on radiology textbooks in 2019. This research had 7 stages of activities which include syntactic, morphological, semantic, and phonetic analysis. In addition, the vocabularies then went through 2 stages of evaluation to check the perfection of words regarding to their writing, meaning, and pronunciation. Furthermore, each vocabulary was given an example of its use in the form of sentences in the context of radiology. Results of the study in the form of a pocket dictionary consisting list of basic radiological vocabulary/terms accompanied by the syntactic categories, the meaning of words in Indonesian language that are in accordance with the scientific context of radiology, phonetic transcription, and examples of the use of words in sentences in the context of radiology are expected to contribute to improving the quality of human resources of radiographers in Indonesia.